A115: Epidemiology of malignant neoplasms of the oral cavity and pharynx in the territory of the Chelyabinsk region. Issue 1 (November 2015) - Dmitrieva, E.; Nurieva, N.
Abstract : The Chelyabinsk region is a classic example of the technologically-saturated region. The index of pollution of atmospheric air is estimated as high. The Chelyabinsk region is among the areas of increased cancer risk. The incidence of head and neck cancer is steadily increasing, accounting for 20–25% of all cancer cases in Russia. Oropharyngeal cancer makes up 5.1% of all cancers. Materials and methods: The object of the study was the population of the Chelyabinsk region. The analysis was conducted according to the materials of the annual reports of the statistics department of the Chelyabinsk district oncology dispensary. Results: Out of the total cancer cases for the population of Chelyabinsk region in 2014, oro-pharyngeal cancer comprised 2.06%, including cancers of the lip (0.35%), tongue (0.47%), major salivary glands (0.22%), other unspecified parts of the mouth (0.52%), oropharynx (0.33%), nasopharynx (0.1%) and hypopharynx (0.07%). From 2008 to 2014, the incidence of oral and pharyngeal cancer among adult population of Chelyabinsk city and Chelyabinsk region showed an 8.8% increase. In the period from 2011 to 2014, the incidence of oral and pharyngeal cancer tended to increase, the overall rise being 71.8%. It should be noted that the oral and pharyngeal cancer incidence was 3 times higher in males than in females in 2013 and 2 times higher in 2014. One of the main indicators that determine the prognosis for the development of cancer, is the extent of tumor at time of diagnosis. Out of the total cancer cases for the population of Chelyabinsk region in 2014, cancer of the oral cavity comprised 1.33%, pharyngeal cancer 0.6%, lip cancer 0.13%, ranking the 17th, 19th and 24th place respectively among the causes of death from all cancers. Analyzing the dynamics of mortality from cancer of the oral cavity and pharynx during the study period, it was revealed that the mortality rate increased by 0.7%. Conclusion: Head and neck tumors are a rare group of clinically and biologically diverse neoplastic diseases. Among the residents of the Chelyabinsk region, men are 2–3 times more susceptible to cancer of the oral cavity and pharynx than women. High mortality rate is due to late referral of patients to specialized clinics; most head and neck cancer patients are diagnosed at advanced stages.